Differences in attitudes to feeding post repair of Gastroschisis and development of a standardized feeding protocol - Donna Hobson; Kaye Spence; Amit Trivedi; Gordon Thomas (BMC, 2019)
Abstract Background The purpose of this study was to examine differences in attitudes to feeding in neonates with Gastroschisis between clinical groups and to develop a standardized feeding protocol. Confusion, inconsistencies in practice and lack of evidence could be contributing to avoidable delays in the establishment of enteral feeds resulting in lengthy requirements for central venous access, dependence on total parenteral nutrition (TPN), increased risk of sepsis, TPN related cholestasis and prolongation in length of hospital stay. Methods A national survey of clinicians (neonatologists, neonatal intensive care nurses and paediatric surgeons), looking after neonates with gastroschisis was undertaken to determine differences in feeding practice post repair. In addition, an audit of practice in one hospital was undertaken to examine variations in practices between clinicians. A feeding protocol was then developed using inputs from surgeons and neonatologists. Results Gastric aspirates and residuals were typically used as indicators of feed readiness and feed tolerance; however, there was very little consistency within and between clinical groups in definitions of tolerance or intolerance of feeds and in how to initiate and progress feeds. A feeding protocol with clear definition of feed readiness and a clear pathway to progression of feeds was developed to help overcome these variations in practice with the possibility that this might reduce the length of stay (LOS) and have other secondary benefits. The protocol included early introduction of enteral feeds particularly direct breast or sucking feeds. Conclusions Wide differences in attitudes to feeding neonates post Gastroschsis repair exist and the need for a consistent protocolized approach was felt. The feeding protocol we developed requires a change of practice and further clinical trials are needed to evaluate its effectiveness.